Komunikační a simulační techniky logopedické Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Kopečný, Petr (Masaryk University Press, 2019)
Title in English: Communication and Simulation Techniques in Speech Therapy: Methodical texts for the MUNI 4.0 project The text focuses on the basic definition of the communication process and the current view of the impaired communication ability. The text presents intervention approaches to the development of the phonetic-phonological language level, focuses on strategies to support the development of articulatory ability and hearing perception in the pre-compulsory education period and selected aids for intervention in the phonetic-phonological language difficulties. Learning support also offers an insight into approaches to pupils in relation to their involvement in a class or group collective, particularly in relation to disruption in communication based on psychogenic factors, but also as a result of serious forms of disability.